Men As Early Childhood Educators. From The Preferred To The Absent. - Sanchidrián-Blanco, María del Carmen; Torres-Sánchez, María Mónica; Molina Poveda, María Dolores; Álvarez-Jiménez, Victoria Eugenia (My University, 2025)
The feminisation of early childhood education is an obvious phenomenon around the world. However, this has not always been the case throughout history. In fact, in the first nursery schools designed to receive and educate poor children between the ages of 2 and 5 whose mothers were unable to care for them, male teachers were preferred for a variety of reasons, but mainly because they were considered more authoritative. In these schools, the presence of the female teacher was mentioned, but she was given a subordinate role, focusing on the care of the children (cleaning and feeding) rather than their education. From then on (1882), only women were allowed access to these posts, which women claimed as their own at a time when their employment opportunities were very limited. The fact that for almost a hundred years nursery teachers have always been women has contributed to a certain loss of professional identity by confusing the teacher with a mother for all. If they had to be women for pre-school education, it is obvious that they had to be women to take care of children under that age, even if it was not professionalised. It was not until the General Education Act of 1970 and, above all, the Constitution of 1978 that men were able to train to become teachers of pre-school education (four- and five-year-olds) and of early childhood education (zero- to six-year-olds) since 1990. However, the possibility of access to training and practice has not been welcomed by male students. Although the current situation of legal non-discrimination is the most widespread, few men opt for early childhood education. This is beginning to be seen as an undesirable situation. Today, there are policies that encourage girls to pursue STEAM, Science, Technology, Arts, Engineering, Arts and Mathematics. In Spain, however, the almost total absence of male teachers in early childhood education has not been discussed and there is no widespread awareness that this is a problem There are countries where advertising campaigns encourage men to study care professions (including education in general and early childhood education in particular). In this journey of almost 200 years, the situation in Spain is analysed at four key moments: 1.The creation of the first pre-schools (1838). 2. Only women can be pre-school teachers (1882). 3. The General Education Act (1970) and the Constitution of 1978. 4. Current proposals to increase the presence of men in early childhood education. The lack of male teachers is tentatively beginning to be seen as a problem, and the first studies are appearing. For each of these moments, we analyse the proposals made and the arguments put forward in the official documents and in the debates that took place, where there were any. Finally, we describe some proposals to put an end to the teacher shortage in early childhood education. As the current situation is not unique to Spain, initiatives from other countries, such as Germany, are included and could be taken into consideration.
Keywords: Educación infantil; Profesores de educación infantil; Male teachers; Early childhood education; Feminization; Gender; Spain